Efeito da farinha de resíduo de Peixe e de Frango no desempenho e na composição corporal de juvenis de Tambaqui, Colossoma macropomum (Cuvier, 1818) - Terrazas, Werner Damião Morhy; Pereira Filho, Manoel; Pereira, Maria Inêz de Oliveira (Acta Amazonica, 2002)
This study attempts to verify the effect of fish meal (FM), poultry meal (PM) and a combination of these ingredients on the weight gain and body composition of juvenile tambaqui, Colossoma macropomum. The experiment was conducted in a complete randomized design using four treatments, each one with four replicates. The test diets were as follows: R1 = 21% FM; R2 = 14% FM + 7% PM; R3 = 7% FM + 14% PM and R4 = 21% PM. Fish were stocked in 16 tanks at a density of 16 fish per tank. Fish initial mean weight was 13.9±0.4g. After 120 days, the results showed no significant differences among treatments (p>0.05) although an improvement in the weight gain was observed when FM and PM were used in combination.
Effect of different levels of Fish meal and Chicken by-product meal in the weight gain and body composition of Tambaqui (Colossoma macropomum)
Keywords: Colossoma Macropomum; Fish Meal; Chicken Meal; Colossoma Macropomum; Farinha De Resíduo De Peixe; Farinha De Resíduo De Frango